PENINGKATAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI MUSIK - KOMALASARI, DEWI (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
Aims this study is to improve the writing skills of number symbols through music and movement to children ages 4-5 years. The research was conducted in TK/RA Diponegoro, Village Bagbogo Tanjunganom, Nganjuk, East Java in May-June 2012. The method used is action research conducted by one sirklus which consists of 6 sessions. Subjects were in kindergarten/RA class A3 Diponegoro, Village Bagbogo Tanjunganom, Nganjuk, East Java, including 29 children. Percentage analysis of the data used in this study based on the consensus of the investigators and collaborators are the achievements of the average value in the cycle I finally reached 23.8%. Analysis of data by looking at the percentage increase in the ability to know the symbol of the cycle I was 14.13%. From the data on average class pretest only 64.31 to 78.44 on average posttes. Based on the presentation of an increase in this study, the hypothesis can be accepted otherwise. Can be concluded that the writing skills of number symbols to children ages 4-5 years can be increased through music and movement with the song "a combination of lines and a circle".Keywords: writing skills of number symbols, music and movement